Forestry and the Carbon Market Response to Stabilize Climate - Massimo Tavoni; Valentina Bosetti; Brent Sohngen (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper investigates the potential contribution of forestry management in meeting a CO2 stabilization policy of 550 ppmv by 2100. In order to assess the optimal response of the carbon market to forest sequestration we couple two global models. An energy-economy-climate model for the study of climate policies is linked with a detailed forestry model through an iterative procedure to provide the optimal abatement strategy. Results show that forestry is a determinant abatement option and could lead to significantly lower policy costs if included. Linking forestry management to the carbon market has the potential to delay the policy burden, and is expected to reduce the price of carbon of 40% by 2050. Biological sequestration will mostly come from avoided deforestation in tropical forests rich countries. The inclusion of this mitigation option is demonstrated to crowd out some of the traditional abatement in the energy sector and to lessen induced technological change in clean technologies.
Keywords: Q23; Q52; Q55; 330; Forestry; Climate Policy; Technological Innovation